Reanalysis of historic elemental speciation filters to investigate the presence of fibrous mineral particles using microscopy techniques - Talbot, Nick; Dirks, Kim N.; Fan, Wendy; Patel, Hamesh; Costello, Seosamh B.; Brook, Martin; Davy, Perry (Frontiers in Chemistry, 2022)
A case is presented for the value of archiving air quality filters to allow for retrospective analysis of emerging contaminants, that is filter constituents not considered to be harmful (and thus not identified or quantified specifically) at the time of collection but subsequently considered to be of interest. As an example, filters from a 20-year historical archive consisting of 16,000 filters from three sites across Auckland are re-examined for the presence of elongated mineral fibres known to be present in rock across the city. Originally collected for the purpose of the source apportionment of particulate matter, 10 filters from each of the three sites were chosen for reanalysis based on their high silica and aluminium content, and thus considered more likely to contain fibre-like particles (FLP). These filters were analysed using various microscopic methods, including phase contrast microscopy (PCM), scanning electron microscopy (SEM) and energy-dispersive x-ray spectroscopy (EDS). The results show that although the commonly used fibrous polytetrafluoroethylene (PTFE) material of the filters may hamper the visual identification of any fibre-like particles under a certain length, their key components are able to be identified using a combination of PCM and SEM when they are of a suitable dimension and have settled in a certain orientation on the filter. In this case, the use of EDS confirmed the silicon content of the fibres and also revealed elemental spectra. Although the exact identification of the mineral fibre is uncertain, the EDS scan is consistent with hazardous zeolites such as erionite, known to be present in the rock found in Auckland. This study highlights the value in maintaining filter archives for the purpose of investigating the historical evolution of emerging atmospheric pollutants.